Understanding organizational readiness for knowledge management in the Malaysian public sector organization: a proposed framework - Abdul Karim, Nor Shahriza; Mohammad, Norshidah; Abdullah, Lili Marziana; Mohamed Razi, Mohamed Jalaldeen (2011)
Knowledge Management (KM) is recognized by many organizations as an important tool in promoting competitiveness and organizational sustainability. However, it has been stressed that the organizational readiness for KM needs to be assessed before embarking on the actual implementation. A comprehensive review of the KM literature reveals that very limited information is available on KM readiness. In view of this, a comprehensive research model for organizational readiness for KM process implementation is proposed. Based on this model, the extent of KM readiness in Malaysian public sector organizations can be investigated. The methods employed for the overall research will be focus group interviews and survey.